Impact of Serum Apolipoprotein A-I on Prognosis and Bevacizumab Efficacy in Patients with Metastatic Colorectal Cancer: a Propensity Score-Matched Analysis() - Quan, Qi (Transl Oncol, 2017)
PURPOSE: We aimed to investigate the role of apolipoprotein A-I (ApoA-I) as a predictor of prognosis and treatment efficacy of bevacizumab in patients with metastatic colorectal cancer (mCRC) treated with first-line chemotherapy with or without bevacizumab. METHODS: We conducted a retrospective study on consecutive patients who were diagnosed with mCRC at Sun Yat-sen University Cancer Center. According to their pretreatment ApoA-I level, patients were divided into low– and high–ApoA-I groups. Propensity score-matched method was performed to balance baseline characteristics between two groups. Based on whether they accepted bevacizumab as a first-line therapy, patients were further divided into the chemo + bevacizumab group and the chemo group. Overall survival (OS) and progression-free survival (PFS) were assessed with Kaplan-Meier method, log-rank test, and Cox regression. RESULTS: The optimal cutoff value for the ApoA-I level was determined to be 1.105 g/l. In the propensity-matched cohort of 508 patients, low ApoA-I was significantly associated with inferior OS (P < .001) and PFS (P < .001) than high ApoA-I. Multivariate analysis showed that ApoA-I level was an independent prognostic maker of OS (P < .001) and PFS (P = .001). PFS (P < .001) in either the high– or low–ApoA-I groups could be extended significantly after the administration of bevacizumab, and patients with a high ApoA-I level also had a better OS in the chemo + bevacizumab group than the chemo group (P = .049). CONCLUSIONS: Patients with a low ApoA-I level have poor prognoses, and they did not display an OS benefit from bevacizumab.